Preservation of historical memory in rostov-on-don's toponymic space: an example of the assign-ment of honorary names to schools - Anton V. Aver'janov; Georgiy A. Shvidkoy (Кавказология, 2023)
Researchers consider issues related to the study of historical memory in a broad context, because the perception and display of its individual plots can be studied from various angles, both material in the form of, for example, a memorial space, and public and state practices, such as holding festive events. Research into toponymic space entails direct touch with the sphere of historical memory. With this phrasing of the topic, the toponymy of Rostov-on-Don appears to be a very interesting route for thinking about specific practices of conserving historical memory, such as naming schools after historical figures. Being a part of the general toponymic space of the city, they are a vivid marker of how the practices of implementing toponymic policy and preserving historical memory interact at the present stage. The authors of this article believe that studying toponymic space entails direct work on the study of the key subjects of historical memory, which are fixed in public space, by designating not just streets or squares, but also individual institutions. Based on the analysis of the complex of honorary names of Rostov-on-Don schools, the time of their appearance, as well as the semantic load, it seems natural to draw conclusions about the most significant and relevant subjects of historical memory preserved in the 1990s-2020s on the map of the capital of the South and the gates of the North Caucasus.